The Association of Pre-treatment Peripheral Blood Markers with Survival in Patients with Pancreatic Cancer - (:unkn) unknown (H G E UPDATE MEDICAL PUBLISHING S A, 2010)
Background/Aims: The aim of the study is to assess the prognostic value of pretreatment lymphocyte, neutrophil, platelet counts, mean platelet volume (MPV), platelet to lymphocyte ratio (PLR) and neutrophil to lymphocyte ratio (NLR) in patients with pancreatic cancer. Methodology: A total of 65 eligible patients were included in the study and retrospectively reviewed. Pre-treatment hematological parameters (platelet, lymphocyte, neutrophil counts, and mean platelet volume) and tumor marker (CA 199) levels were recorded. NLR was calculated by dividing the neutrophil count value by the number of lymphocytes. PLR was also calculated in a similar manner by dividing the platelet count value by the number of lymphocytes. Results: One-year survival was 22.3% and the median survival time was 7 months (95% CI, 5.7-8.2) in the study group. Patients with a NLR value of < 5 had a significantly higher median survival duration compared to those with a NLR value of >= 5 (p= 0.015). All other hematological variables were not significantly different. Conclusions: In patients with pancreatic cancer, pretreatment NLR may be use as a prognostic factor in pancreatic cancer patients. Further studies with larger patient cohorts are warranted to to better clarify the prognostic value of pre-treatment peripheral blood counts in patients with cancer.
Keywords: Peripheral blood count; neutrophil; platelet; lymphocyte; pancreatic carcinoma; platelet to lymphocyte ratio, neutrophil to lymphocyte ratio, prognosis; PREOPERATIVE PLATELET COUNT; LONG-TERM SURVIVAL; LYMPHOCYTE RATIO; PROGNOSTIC-FACTORS; PREDICTS SURVIVAL; DUCTAL ADENOCARCINOMA; CURATIVE RESECTION; THROMBOCYTOSIS; NEUTROPHIL; ANGIOGENESIS